Anti-Oxidant Efficacy of Ginger Containing Dentifrice in the Control of Biofilm Induced Gingivitis. ( Randomized Parallel Clinical Trial ) (Mustansiria Dental Journal, 2023)
Background: Gingivitis induced by biofilm is one of the most prevalent periodontal diseases. Due to their antimicrobial, anti-inflammatory, antioxidant, and other multipotent effects, a number of traditional medicinal plants are revered as pharmaceutical alternatives. Aim: The aim of the current study was to assess the antioxidant efficacy of ginger containing dentifrice in control patients with biofilm induced gingivitis.Materials and methods: In a double-blind, randomized, parallel clinical trial, one hundred adults suffering from gingivitis caused by dental biofilm were split into two groups and given either a ginger-containing or a control dentifrice to use for three months. Clinically, periodontal assessment and saliva collection were performed at the baseline visit and after three months of toothpaste use in order to determine the superoxide dismutase level.Results: Ginger containing dentifrices showed a significantly improved in plaque (0.216+0.069) and bleeding on probing (7.818+7.339) index scores. In addition, a significant increase (22.082+1.510) in the level of SOD antioxidant after 3months compared with control dentifrice. Conclusion: Compared to conventional dentifrices, herbal dentifrices demonstrated promising outcomes.